Implementation of the official document management policy within the north sulawesi provincial government - Alfrets R. Owu; Maria H. Pratiknjo; Jhony R. E. Tampi (LEGAL BRIEF, 2023)
This study aims to analyze the implementation of official document arrangement (TND) policies within the North Sulawesi provincial government. This study uses a qualitative descriptive method based on Grindle's theory with indicators consisting of policy content and policy environment. The research informants were taken using a purposive sampling technique, totaling 8 informants. Data analysis uses data reduction, data presentation and conclusion drawing. The results showed that the management of official document within the North Sulawesi provincial government was based on Governor Regulation Number 34 of 2010 which was based on the Regulation of the Minister of Home Affairs Number 54 of 2009. The management of the official document arrangement is still hampered by a number of issues, such as each Regional Apparatus Work Unit (SKPD) use of a non-uniform format and the usage of logos and stamps that do not adhere to established guidelines. Instead, the format is governed by the preferences of the specific SKPD leaders. The North Sulawesi government has decided to employ an electronic-based government system (PBSE); however, they still manage official documents manually. The use of an electronic/digital system can reduce the need for paper and ink, speed up the correspondence system, and make the process of storing archives easier because using a manual technique runs the risk of damaging paper records due to ageing.